The positive psychology of laughter and humour - Gonot-Schoupinsky, Freda; Neal, Meav; Carson, Jerome (Emerald Publishing Limited, 2024)
Humour is officially recognized in positive psychology as one of the 24 'character strengths'. However, laughter has an uneasy relationship with positive psychology, despite being key to communicating joy and happiness.The Positive Psychology of Laughter and Humour corrects this disconnect by combining academic insight with real-world experience. Drawing on the authors' diverse backgrounds and expertise, this is the first academic volume dedicated to the rarely discussed topic of laughter and humour in positive psychology. Freda Gonot-Schoupinsky, Merv Neal and Jerome Carson demonstrate how laughter and humour differ, and how both can be applied within positive psychology to boost mood and maintain positive outcomes.The Positive Psychology of Laughter and Humour includes case studies and real-world insight as well as providing a methodological and theoretical background to the topic, giving rigorous theoretical and methodological insight for researchers, and including pedagogical sections in each chapter useful for teachers and researchers.
Keywords: Laughter -- Psychological aspects.; Wit and humor -- Psychological aspects.; Psychology -- General.; Psychology: emotions.; Psychology.; elektronické knihy; electronic books